The Difference Between Everyday Listening and Academic Listening in English Learning - Saragih, Nur Annisa Ameliya; Surbakti, Alika Nathania; Hafida, Isma; Siregar, Deasy Yunita; Andini, Atika Dwi (PT. Kreasi Karya Majakata, 2026)
Listening is widely recognized as a fundamental skill in English language learning because it serves as the primary channel through which learners receive linguistic input. Through listening, learners are exposed to vocabulary, grammatical structures, pronunciation patterns, and discourse features that shape overall language development. In everyday life, listening enables individuals to engage in social interaction, interpret meaning, and respond appropriately in informal communication. In academic contexts, particularly at the university level, listening plays a more complex and demanding role, as it supports learning, knowledge construction, and academic success. Despite its importance, many English as a Foreign Language (EFL) learners assume that listening skills developed through daily communication are sufficient for academic purposes. This assumption often leads to difficulties when learners encounter academic spoken discourse, such as lectures, academic discussions, and presentations, which are linguistically denser and cognitively more demanding. This article aims to examine the differences between everyday listening and academic listening in English learning. Using a qualitative descriptive approach based on a literature review, this study synthesizes theoretical perspectives and empirical findings related to listening comprehension. The findings indicate that everyday listening is spontaneous, context-dependent, and interaction-oriented, whereas academic listening is formal, goal-driven, and requires specific cognitive and strategic skills, including identifying main ideas, recognizing discourse structure, and taking notes. The article argues that academic listening competence does not automatically develop from everyday listening experience and therefore requires explicit attention in English